Effects of Different Molecular Weight Polysaccharides From Dendrobium officinale Kimura & Migo on Human Colorectal Cancer and Transcriptome Analysis of Differentially Expressed Genes - Tao, Shengchang; Ren, Zhiyao; Yang, Zerui; Duan, Shuna; Wan, Zhongxian; Huang, Jiahui; Liu, Chenxing; Wei, Gang (Frontiers in Pharmacology, 2021)
We investigated the anti-tumor effects of four fractions of Dendrobium officinale Kimura & Migo (D. officinale) polysaccharides with different molecular weights (Mw), Astragalus membranaceus polysaccharides (APS) and Lentinus edodes polysaccharides (LNT) on colorectal cancer (CRC) using a zebrafish xenograft model. Transcriptome sequencing was done to further explore the possible anti-tumor mechanisms of D. officinale polysaccharides. Fractions of D. officinale polysaccharides, LNT, and APS could significantly inhibit the growth of HT-29 cells in a zebrafish xenograft model. One fraction of D. officinale polysaccharides called DOPW-1 (Mw of 389.98 kDa) exhibited the strongest tumor inhibition. Compared with the control group, RNA-seq revealed that the DOPW-1-treated experimental group had 119 differentially expressed genes (DEGs), of which 45 had upregulated expression and 74 had downregulated expression. Analyses using the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes suggested that the pathway “Apoptosis-multiple species” was the most significantly enriched. Our data indicated that: (i) fractions of D. officinale polysaccharides of Mw 389.98 kDa were the most suitable against CRC; (ii) DOPW-1 could be developed into a clinical agent against CRC; (iii) an apoptosis pathway is important for DOPW-1 to inhibit the proliferation of HT-29 cells.